The Effectiveness of Using Digital Media in Teaching English Writing Skills for Elementary School Students - Maryanto; Hersulastuti; Purwo Haryono (Universitas Muhammadiyah Sorong, 2025)
This study aims to determine effectiveness of digital media in teaching English writing skills in class IV students at SDIT Al Hasna Klaten. This research is a type of quantitative research, using an experimental research form. The experimental research method is defined as a research method used to determine the effect of certain treatments on other treatments in conditions that can be controlled, by giving certain treatments to the experimental group and providing a control group as a comparison of pretest-posttest control group design. Based on data analysis, it can be concluded that the learning method using digital media has an effect on learning outcomes. This is indicated by the results of the posttest t-test of students by obtaining a posttest value of Sig. (2-tailed) greater than the alpha value of the study, so it can be concluded that H0 of this study is rejected and H1 is accepted. The learning outcomes of students who use learning with digital media are higher than those who use conventional learning. The increase in English writing skills shows that the average in the experimental class is in the medium category, while the average in the control class is in the low category. This shows that different treatments cause different final results. It can be said that the use of learning with digital media in the experimental class is more effective in improving students' English writing skills compared to classes that use a conventional approach in English subjects for grade IV.